THE INTERFERENCE OF INDONESIAN ON ENGLISH SECOND LANGUAGE WRITING - Iman, Topan Rahmatul (JOLLT Journal of Languages and Language Teaching, 2020)
Language transfer means the application of knowledge and understanding of a source language on a target language. Dissimilarities between the source language and the target language could result in a negative transfer. This essay aims to investigate the interference of Indonesian language on English second language writing regarding the order of noun phrase constituents, number marking, and verb tenses. The results presented in this essay were based on three elicitation tasks that were answered by 20 Indonesian students who studied English at a senior high school in Sumbawa Regency, Indonesia. Their ages were between 15 to 18 years old.  The participants were given a test that consisted of three elicitation tasks focusing on sentence writing. The results showed that the negative transfer was still found in the students? writing. However, the students may make mistakes since they had a lack of knowledge, or because they were unable to apply what they knew in their writing.